Veterinary clinical parasitology - Zajac, Anne M.; Conboy, Gary A. (Wiley-Blackwell, 2012)
Veterinary Clinical Parasitology, Eighth Edition, prepared under the auspices of the American Association of Veterinary Parasitologists (AAVP), emphasizes the morphologic identification of both internal and external parasites of domestic animals